Thermodynamics of Mixed Electrolyte solutions: An EMF study of Activity and Osmotic coefficients of NaCl in NaCl-Ca(NO3)2-H2O system at 25, 35 and 450C (Journal of Pharmaceutical Negative Results, 2023)
Electromotive force measurements have been carried out on the system NaCl-Ca(NO3)2-H2O at I = 0.5,1.0, 2.0 and 3.0 mol kg-1 and at 25, 35 and 45oC using a cell consisting of sodium ion-selective electrode and an Ag/AgCl electrode. The data are analysed using the Pitzer and Harned equations. The osmotic coefficients, activity coefficients of Ca (NO3)2 and excess free energies of the aqueous mixtures have been estimated at 25oC.Pitzer formulism made use to describe the properties of concentrated electrolyte mixtures.